The Role of Islamic Education Teachers in Instilling Student Discipline - K Kamaruddin; Andi Anto Patak (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2018)
Education is an effort to develop the potential that exists in humans. Teachers are an integral part of educational resources that explore the educational success. A teacher who plays a role in the intellectual and mental coaching of students is expected to instill discipline and attitude towards students. This study aims to explore the role of Islamic education teachers in instilling student discipline. The method of this study is qualitative to explore the state of the object of the study. Five of the Islamic education teachers participated in this study. The instrument used in this study is interview protocols. The results of this study showed that Islamic education teachers are competent in carrying out their roles. Likewise in their role in instilling students’ discipline, Islamic education teachers are informers, organizers, motivators, initiators, and evaluators.